2017
DOI: 10.1186/s12939-017-0601-3
|View full text |Cite
|
Sign up to set email alerts
|

Access to treatment for Hepatitis C among injection drug users: results from the cross-sectional HOPE IV study

Abstract: BackgroundEvidence suggests that Greece is among the European countries with increased trend in HCV prevalence among injecting drug users (IDUs) from 2008 to 2014. Nonetheless, the access of IDUs to treatment for Hepatitis C Virus (HCV) is very limited while the risk of co-infection and transmission remains high. In an effort to better understand the inhibitors to HCV treatment, the present study aimed to investigate the main barriers to access in a sample of IDUs.MethodsThe cross-sectional study was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
(56 reference statements)
4
11
0
1
Order By: Relevance
“…For example, in Patras, although there is a well-organized PWID substitution unit, there is no FibroScan available, so patients have to travel in order to have elastography measurements. Thus, consistently with the literature [ 23 ], our data revealed that in some settings there is significant lack of coverage of services or barriers when patients try to access services, mainly for geographical reasons.…”
Section: Discussionsupporting
confidence: 89%
“…For example, in Patras, although there is a well-organized PWID substitution unit, there is no FibroScan available, so patients have to travel in order to have elastography measurements. Thus, consistently with the literature [ 23 ], our data revealed that in some settings there is significant lack of coverage of services or barriers when patients try to access services, mainly for geographical reasons.…”
Section: Discussionsupporting
confidence: 89%
“…MethodsA cross-sectional study was carried out between February and April 2019 to assess barriers in access to HIV care faced by people living with HIV. An online, self-reporting questionnaire was developed on the basis of the HOPE I, II, III and IV(6,7,8,9) studies tool and adapted to the specific clinical and societal characteristics of HIV. The questionnaire consists of three main sections.…”
mentioning
confidence: 99%
“…[ 25 , 26 ] In the modern CoC, this concern is likely driven primarily by social factors including unstable housing, mental illness, or active alcohol and substance abuse rather than severe side effects from the medication. [ 14 , 25 , 27 ] Given the high prescription, initiation, and completion rates seen in the population in our study, concern regarding non-adherence may not be warranted in all settings. To facilitate initiation and completion of HCV treatment, providers should place an emphasis on engaging this population with social workers, case managers, and addiction counselors.…”
Section: Discussionmentioning
confidence: 97%